2019
DOI: 10.17533/udea.iee.v37n2e07
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a nursing intervention to diminish preoperative anxiety in patients programmed for knee replacement surgery: Preventive controlled and randomized clinical trial

Abstract: Objective. This work was conducted to determine the effectiveness of a nursing intervention, based on the motivational interview, to diminish preoperative anxiety in patients programmed for knee replacement surgery.Methods. Preventive type controlled and randomized clinical trial, on a sample of 56 patients programmed for knee replacement surgery in a clinic in Girardot (Colombia). Random assignment was made: an intervention group (n=28) and a control group (n=28). The six-question Amsterdam Preoperative Anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
(17 reference statements)
0
14
0
3
Order By: Relevance
“…The characteristics of the included studies by type of intervention, aggregate data from the included studies by type of intervention, RoB assessment, summary of findings, excluded studies, studies that fit the inclusion criteria but had no usable data, and relevant protocols of ongoing or unpublished studies are shown in the online supplemental digital content. We identified eight types of interventions administered in the preoperative period: nutritional (51 studies),30–80 respiratory (30 interventions of 29 studies)81–109 exercise (27 studies),110–136 multimodal (25 studies),100 108 137–159 educational (17 studies),160–176 psychological (16 studies),177–192 smoking and alcohol cessation (7 studies)193–199 and pharmacological (5 studies)200–204 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies by type of intervention, aggregate data from the included studies by type of intervention, RoB assessment, summary of findings, excluded studies, studies that fit the inclusion criteria but had no usable data, and relevant protocols of ongoing or unpublished studies are shown in the online supplemental digital content. We identified eight types of interventions administered in the preoperative period: nutritional (51 studies),30–80 respiratory (30 interventions of 29 studies)81–109 exercise (27 studies),110–136 multimodal (25 studies),100 108 137–159 educational (17 studies),160–176 psychological (16 studies),177–192 smoking and alcohol cessation (7 studies)193–199 and pharmacological (5 studies)200–204 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the past, it was di cult for routine nursing to meet the needs of such special groups of patients. It is necessary to provide patients with more satisfactory, more complete, and more comprehensive nursing services through innovative nursing models so as to ensure the quality of nursing and to meet the needs of patients [13]. With the promotion of the concept of fast recovery, scholars have found that it can greatly improve the prognosis and promote postoperative recovery [14].…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing a total knee arthroplasty, a total of 3 sessions of nursing intervention were conducted during the six-week period prior to surgery, and anxiety scores were significantly reduced compared to controls. 20 In this study, 76.0% of all patients reported experiencing the greatest level of anxiety from the night before surgery to the day of surgery. Thus, intensive intervention to reduce anxiety during this time could help relieve anxiety in geriatric patients.…”
Section: Discussionmentioning
confidence: 59%